The Role of Inflammatory Parameters and Antibody Seroconversion on COVID-19 Outcomes in Patients with Central Obesity - Wafa, Syahidatul; Tahapary, Dicky Levenus; Yunihastuti, Evy; Wibowo, Heri; Rumende, Cleopas Martin; Harimurti, Kuntjoro; Suastika, Ketut; Kurniawan, Farid; Kartika, Rona; Pradnjaparamita, Tika; Harbuwono, Dante Saksono (Acta medica Indonesiana, 2024)
Central obesity increases the risk of developing poor outcomes of COVID-19. The pro-inflammatory state and antibody dysfunction are thought to contribute to poor outcomes; however, the evidence is unclear. This is a cohort study among COVID-19 patients with central obesity in Dr. Cipto Mangunkusumo National General Hospital Jakarta, Indonesia, during the early phase of the COVID-19 pandemic. Our study is a part of the COVID-19, Aging, and Cardiometabolic Risk Factors (CARAMEL) study. From the CARAMEL study, we selected adult non-ICU/HCU inpatient subjects with central obesity that met inclusion/exclusion criteria, collected clinical and anthropometric data, and measured inflammatory cytokines and IgG S-RBD SARS-CoV-2 antibody titers from a stored sample taken at day 2 of hospitalization. The poor clinical outcome of hospitalization was observed. We used the Mann-Whitney test to analyse non-normally distributed data, and T-test for normally-distributed data. The adjusted-relative risk of negative seroconversion antibody for poor outcomes was analysed using logistic regression. 23 of 178 (12.9%) subjects developed poor clinical outcomes during hospitalization. Subjects with poor outcomes had a higher visceral fat area (14.5 vs. 11, p < 0.05), waist circumference and BMI. The level of CRP, pro-inflammatory cytokines (IL-6 and MCP-1) and anti-inflammatory cytokines (IL-1Ra, IL-4, and IL-10) were significantly higher in subjects with poor outcomes, alongside with the lower antibody titer in subjects with poor outcomes. Antibody seroconversion failure increased the risk of developing poor outcomes (aRR 2.696, 95% CI 1.024-7.101), after adjusting for age and sex. In COVID-19 patients with central obesity, we confirmed the association between higher pro- and anti-inflammatory parameters, and lower SARS-CoV-2 antibody with poor outcomes of COVID-19.